FIELD ELECTRON EMISSION PROPERTIES OF VERTICALLY ALIGNED CARBON NANOTUBES SYNTHESIZED FROM PALM OIL PRECURSOR - Abu Bakar, Suriani (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2016)
Vertically aligned carbon nanotubes (VACNT) synthesized at different ferrocene concentration by thermal decomposition of bio-hydrocarbon source namely palm oil were investigated for field electron emission application. The ferrocene concentration ranges from 0.5 to 3.5 wt% and the as-prepared VACNT were characterized using field emission scanning electron microscopy and micro-Raman spectroscopy. It was clearly shown that a controlled increase in the mixture of ferrocene and palm oil was important in improving field emission behaviour. The samples synthesized using 2.5 wt% ferrocene concentration proves to be the optimum concentration as for lowest turn-on (corresponding to the current density of 0.1 mAcm-2) and threshold field (corresponding to the current density of 1 mAcm-2) at 3.17 and 4.07 VÂµm-1 respectively in comparison with other concentration. The sample also demonstrates highest peak current of 8.0 mAcm-2 at a field of 5.5 VÂµm-1 as well as less degradation during one hour emission stability testing.Â Key words: Carbon Nanotubes, Palm oil, Chemical vapor deposition, Field electron emission, Scanning electron microscopy, Raman spectra, catalytic methods.